Managing of communication processes in social media by the cities of Metropolitan Association of Upper Silesia and their majors - Piechota, Grażyna (Journal of Public Governance, 2013)
The importance of social media used for local communication is growing. Local leaders and municipal administrations use social media for passing certain information to the local community. The subject of the article is the analysis of how some mayors and their administrations communicate with local communities, what goals they want to achieve using selected communication channels and what information they publish in social media. The analysis presented in the article was based on quantitative and qualitative research carried out in 2012 in cities of the Silesian Metropolis and among their mayors.